Micropapillary pattern is associated with the development of brain metastases and the reduction of survival time in EGFR-mutation lung adenocarcinoma patients with surgery. (March 2020) - Li, Changhui; Shen, Yinchen; Hu, Fang; Chu, Tianqing; Yang, Xiaohua; Shao, Jinchen; Zheng, Xiaoxuan; Xu, Jianlin; Zhang, Hai; Han, Baohui; Zhong, Hua; Zhang, Xueyan
Highlights: MIP was an independent poor prognostic factor for the increase of BM rate. MIP could shorten the time of BM development after surgery. MIP was related to the earlier recurrence and shortened survival time. Abstract: Objective: The role of micropapillary pattern (MIP) in EGFR-mutated NSCLC patients with brain metastases (BM) after complete surgical resection still remains unclear. Therefore, a retrospective study was conducted to evaluate the role of MIP in those patients. Methods: This study included 332 stage I-III patients with EGFR-mutant lung adenocarcinoma and complete resection. Patients were classified in four groups: the MIP-positive patients without BM development, the MIP-negative patients without BM development, the MIP-positive patients with BM development and the MIP-negative patients with BM development. Intracranial disease-free survival (iDFS), systemic disease-free survival (DFS) and overall survival (OS) were evaluated. Results: The median OS in the whole group was 70 months. The patients with MIP show inferior DFS (13 months vs. 22 months; P < 0.001) and OS (56 months vs. 74 months; P < 0.001). Furthermore, BM development was more likely to be found in patients with MIP (P = 0.001). In addition, the MIP-positive patients showed a significantly shorter iDFS compared with MIP-negative patients (14.5 months vs. 26 months; P < 0.001). Furthermore, the MIP-positive patients had significantly inferior iDFS in both BM as first line development groups (13 months vs. 19 months; P < 0.001) and BM as non-first line development groups (18 months vs. 33 months; P = 0.007). Conclusions: MIP was related to the earlier recurrence and shortened survival time. In addition, MIP was an independent poor prognostic factor for the increase of BM rate and the shortened time of BM development after surgery.